Identification and Function of Myeloid Differentiation Factor 88 (MyD88) in Litopenaeus vannamei - Zhang, Shuang (Public Library of Science, 2012)

(untitled)
Myeloid differentiation factor 88 (MyD88) is a universal and essential signaling protein in Toll-like receptor/interleukin-1 receptor-induced activation of nuclear factor-kappa B. In this study, two MyD88 protein variants (LvMyD88 and LvMyD88-1) were identified in Litopenaeus vannamei. The LvMyD88 cDNA is 1,848 bp in length and contains an open reading frame (ORF) of 1,428 bp, whereas the LvMyD88-1 cDNA is 1,719 bp in length and has an ORF of 1,299 bp. Both variants encode proteins with death and Toll/interleukin-1 receptor domains and share 91% sequence identity. In healthy L. vannamei, the LvMyD88 genes were highly expressed in hemocytes but at a low level in the hepatopancreas. The LvMyD88s expression was induced in hemocytes after challenge with lipopolysaccharide, CpG-ODN2006, Vibrio parahaemolyticus, Staphyloccocus aureus, and white spot syndrome virus, but not by poly I∶C. Overexpression of LvMyD88 and LvMyD88-1 in Drosophila Schneider 2 cells led to activation of antimicrobial peptide genes and wsv069 (ie1), wsv303, and wsv371. These results suggested that LvMyD88 may play a role in antibacterial and antiviral response in L. vannamei. To our knowledge, this is the first report on MyD88 in shrimp and a variant of MyD88 gene in invertebrates.